TI_GERICHTE 12.2019.203 vom 18. Mai 2020 , Sentenza straniera - riconoscimento - exequatur - legittimazione attiva - TI Tribunale d'appello (2020)
Sentenza straniera - riconoscimento - exequatur - legittimazione attiva